Socio-Economic and Demographic Correlates of Labour Force Participation in Ghana - Tawiah, N.C. (University of Ghana, 2015)
The study examines socio-economic and demographic correlates of labour force participation in Ghana. Data from the 2010 Ghana Population and Housing Census were used for this study. The study focused on the population aged between 15 to 64 years (who were considered to be within the active working age). The analysis was done at three levels namely, univariate, bivariate and multivariate levels. Graphs, frequencies and percentages were used to describe the characteristics of the respondents at the univariate level. The results show that 72.8% of the study group was in the labour force, while the remaining 27.2% was not in the labour force. Also, there were more people in urban areas than in rural areas. Again, there were more people in the youngest age group (15-24 years) than any of the other age groups. At the bivariate level, cross tabulations and chi-square tests were used to test the relationships between the predictor variables and labour force participation. The results indicate that males participated more in the labour force than females. Also, married men and women participated more in the labour force than their unmarried counterparts. However, among the married, married men participated more in the labour force than married women. The binary logistic regression model was used at the multivariate level to examine how the predictor variables correlated with labour force participation. The results show that nationality was not statistically significant in predicting labour force participation in Ghana. This means that being a Ghanaian or a Non-Ghanaian does not necessarily predict whether one would be in the labour force or not. However, all the other variables namely, age, age squared, sex, marital status, household type, level of education, place of residence, region of residence, ethnicity and religion were statistically significant, hence, they predict whether one would be in the Ghanaian labour force or not. Age was found to have a hump-shaped or concave relationship with labour force participation. Also, education was found to be negatively correlated with labour force participation. The result regarding education is contrary to earlier research findings. However, this could be explained by the fact that significant proportions of the respondents especially, those within 15-24 years were full-time students, and hence, majority of them could not enter the labour force. Again, the population in urban areas are less likely to participate in the labour force than those in rural areas, plausible reasons being that the urban residents are richer and also have enough family support than the rural residents, hence, they can afford the luxury of not working if they could not get good jobs. The results also show that married men and women are more likely to participate in the labour force than their unmarried counterparts.
Thesis(M.A)-University of Ghana, 2015
Keywords: Socio-Economic; Demographic Correlates; Labour Force Participation; Ghana